Feministische Visionen vor und nach 1989 Geschlecht, Medien und Aktivismen in der DDR, BRD und im östlichen Europa - Aleksander, Karin; Auga, Ulrike; Dvorakk, Elisaveta; Heft, Kathleen; Jähnert, Gabriele; Schimkat, Heike (Verlag Barbara Budrich, 2022)
How did gender discourses challenge social relations before and after 1989? How did actors intervene in powerful orders? How are feminist visions incorporated into contemporary activisms? This volume examines feminist, queer, and artistic practices of resistance as well as media discourses and attributions of GDR gender images from intersectional, postcolonial, and post-secular perspectives. In addition, the development of gender studies in Eastern Europe will be examined.